Leadership styles and the retention of transaction managers in South African investment banks - Stellenberg, Cheryll (University of the Witwatersrand, Johannesburg, 2024)
This research aims to explore the relationship between transformational leadership and the retention of highly skilled employees, specifically within the context of transaction managers in South African investment banks. While existing studies have established the positive impact of transformational leadership on employee retention, there is a notable gap in the literature regarding its application to highly skilled professionals in the transaction management role within the South African investment banking sector. This study seeks to fill this void by examining the extent to which transformational leadership practices contribute to the retention of these specialised professionals. The study used a qualitative method, conducting semi-structured interviews with transaction managers from several banks. The qualitative Delve tool data analysis programme was employed to conduct an inductive investigation into the truth behind the four pillars of transformational leadership and its impact on the retention of transaction managers in Johannesburg banks' investment banking divisions. The following four pillars were also chosen as higher-order themes: (1) idealised influence, exemplified by a transformational leader serving as a role model; (2) inspirational motivation, reflecting a leader's ability to effectively communicate a compelling vision and motivate followers to align their goals with the company's; (3) intellectual stimulation, denoting a leader engaging followers' minds in challenging activities; and (4) individualised consideration, signifying a leader actively observing and addressing followers' expressed needs. Retention is a top priority for any organisation, with a well-designed plan aiming to reduce personnel turnover rates, resulting in lower expenses and higher revenue and profitability. Simultaneously, such an approach should improve employee morale and productivity. In light of the awareness that individuals often leave due to managers rather than the company itself, there is an increased focus on assessing the level of leadership within organisations. 3 This study seeks to enhance the current knowledge base by offering empirical evidence on how transformational leadership specifically affects the retention of highly skilled transaction managers in South African investment banks. The findings may offer valuable insights for organisational leaders, human resource practitioners, and policymakers in the financial sector, helping them tailor leadership practices to enhance employee retention in this specialised role.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Leadership; Team leaders; Managers; Transformational; Transactional; Transaction managers; UCTD; SDG-8: Decent work and economic growth